ADVANCES IN RESTORATIVE DENTISTRY AND THEIR CLINICAL SIGNIFICANCE (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Restorative dentistry has undergone significant advancements in recent decades, driven by the development of innovative materials, digital technologies, and minimally invasive techniques. These improvements have enhanced both the functional and aesthetic outcomes of dental treatments. Modern restorative procedures aim not only to repair damaged tooth structures but also to preserve healthy tissues and ensure long-term oral health. This article explores recent progress in restorative dentistry, including adhesive systems, composite materials, and computer-aided design and manufacturing (CAD/CAM) technologies. The clinical significance of these advancements is evaluated in terms of treatment efficiency, durability, patient satisfaction, and overall oral health outcomes. Emphasis is also placed on the importance of individualized treatment planning and evidence-based practice in achieving optimal results.